CONFLICTS AND VIOLENCE IN CONTEMPORARY SCHOOLS (Heritage, 2022)
Conflicts and violence are the worldwide spread phenomena, causes of which are saught both within the child`s character and the social settings. Various social interactionsencompass a higherpossibilityof contradistinction of different interests, by which conflicts become an expressive type of social exchange. Violence is in close relation to conflicts in school, which is a complex phenomenon and a state characterized as the use of someforce against someone. It is manifested as an urge, anger, hostility, when one wants to control the other person by using power. Taking into accountthe fact, that there is an increasingnumber ofconflictingandviolentbehaviors in schools in Serbia, the paper treats the current topicwith a focus on the studies of phenomena of conflicts and violence in schools, theircauses, forms, consequences, as well as on prevention and social programs of school violence control.
Keywords: conflicts, agression, violence, school, children